Partner to meet your profit goals. (Manufacturing Engineering)
Machining system buyers can optimize their process choices with the right input. Builders and distributors have entered into "partnerships" with third party suppliers to help buyers select the right combination of tooling, workholding and machine to achieve their product goals. This is more than a "buy here and now" approach to the business of engineering the best possible solution.